Development of the Depressive Symptoms Questionnaire for Children - Berg, Derek H. (Alberta Journal of Educational Research, 2004)
The present study set out to develop a self-report instrument, the Depressive Symptoms Questionnaire (DSQ), for assessing depressed mood in school-aged children. Included were items based on research that reported symptoms of depressed mood in children, items related to negative psychosocial functioning, and items related to self-perceived academic ineffectiveness. Recent research had suggested that negative psychosocial functioning and self-perceived academic ineffectiveness were important to measure depressed mood in school children. After administration to a sample of children in grades 3 to 6, item-scale analyses supported a two-scale 30-item instrument representing depressed mood and academic ineffectiveness. Items that formed the DSQ suggest that sex, age, negative psychosocial functioning, and specific cognitive constructs that undergird self-perceptions of academic ineffectiveness are important when assessing the presence of depressed mood in children. Limitations and implications for future research on assessment of depressed mood in children are discussed.